Investigation and preliminary laboratory study on substrate preference of Schizothorax lantsangensis. (20th October 2021) - Bai, Yanqin; Lin, Chenyu; Huang, Xiaolong; Chen, Li; Shi, Xiaotao
Abstract: The destruction of fish habitat is one of the most important factors in the decline of fish stocks. Substrate is a major component of fish habitat. We examined the substrate preferences of wild adult Schizothorax lantsangensis using both field investigation and laboratory experiments. Field investigation showed that the substrate of S. lantsangensis habitat in parts of the Lancang River consists mainly of sand, gravel, and pebbles. The substrate was categorized into six types according to the particle size using the modified Wentworth classification: sand and silt (diameter < 2 mm), gravel (diameter 2.1–16 mm), pebble (diameter 16.1–32 mm), cobble (diameter 32.1–64 mm), small boulder (diameter 64–128 mm), and boulder (diameter > 128 mm). The substrate preference of S. lantsangensis was determined in the laboratory, using a single factor test, by comparing the residence times of fish in each of six substrates during different time periods. The results showed that S. lantsangensis preferred pebble and cobble substrates. This study provides a reference for the creation of artificial substrate in habitat restoration in the Lancang River.